2014
DOI: 10.2519/jospt.2014.5108
|View full text |Cite|
|
Sign up to set email alerts
|

Short-Term Changes in Neck Pain, Widespread Pressure Pain Sensitivity, and Cervical Range of Motion After the Application of Trigger Point Dry Needling in Patients With Acute Mechanical Neck Pain: A Randomized Clinical Trial

Abstract: Mechanical neck pain has a lifetime and point pre valence almost as high as low back pain 31 and results in substantial disability and economic burden for society. 29 The authors of a recent study 16 found that the prevalence of mechanical neck pain has decreased in the last few years in Spain, potentially attributed to a better understanding and management of the condition. Physical therapy is usually the first management option for individuals with insidious-onset mechanical neck pain. T T METHODS: Seventee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
96
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 47 publications
12
96
6
1
Order By: Relevance
“…This systematic review focused on musculoskeletal pain and included 13 studies: 6 on neck pain (5 on mechanical neck pain 6,24,28,32,43 and 1 on chronic whiplash-associated disorder 38 ), 1 on postoperative shoulder pain, 2 1 on chronic lower back pain, 33 1 on total knee arthroplasty, 27 1 on chronic ankle instability, 35 2 on myofascial pain, 12,36 and 1 on fibromyalgia. 7 Inclusion and exclusion criteria varied greatly across the studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This systematic review focused on musculoskeletal pain and included 13 studies: 6 on neck pain (5 on mechanical neck pain 6,24,28,32,43 and 1 on chronic whiplash-associated disorder 38 ), 1 on postoperative shoulder pain, 2 1 on chronic lower back pain, 33 1 on total knee arthroplasty, 27 1 on chronic ankle instability, 35 2 on myofascial pain, 12,36 and 1 on fibromyalgia. 7 Inclusion and exclusion criteria varied greatly across the studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…After the full review process, 12 studies were selected for inclusion. 2,7,12,24,27,28,32,33,35,36,38,43 After contact with primary authors of included studies, 1 further study was identified for inclusion, 6 resulting in a total of 13 studies. The absolute degree of rater agreement for the first and second stages of the study selection was 86% and 93%, respectively.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Soft tissue interventions such as stretching, manual therapy, and exercises to the deep neck flexors are considered an effective approach to manage neck pain. Dry needling is also used to treat neck pain.…”
Section: Dry Needling As An Interventionmentioning
confidence: 99%
“…When palpated, active MTrPs could elicit referred pain, reproducing the patient's symptoms; whereas, latent MTrPs do not cause a pain that will reproduce the patient's symptoms but could be responsible for tightness of the muscle. [2,3] Dry needling is used for myofascial pain, lower and upper extremity pain, neck pain, back pain, headaches, jaw pain, and migraines, among other conditions. The effects of dry needling in the treatment of knee osteoarthritis has been well documented.…”
Section: Introductionmentioning
confidence: 99%